The element of love - Connealy, Mary (Connealy, Mary. Lumber baron's daughters, 2022)
"After learning their stepfather's plans marry off Laura Stiles and her sisters, they disappear to find matches and claim their father's lumber dynasty. On their expedition they volunteer on a settlement, and Laura sees potential in the local minister. But when secrets buried in his past and the land surface, it will take all they have to keep trouble at bay"--